Population Administration Services and Village Government Performance Analysis - Sussilo, Tri; Sukmana, Hendra (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to provide a thorough examination of Population Administration Services and its impact on the performance of the Banjarbendo Sidoarjo Village Government. Utilizing qualitative descriptive research methods, including interviews, observation, and documentation, the research follows Agus Dwiyanto's analytical framework for data collection, reduction, presentation, and conclusion. The results reveal a commendable performance in implementing Population Administration Services, showcasing high village government productivity. The assessment of service quality, encompassing nine essential elements, demonstrates overall effectiveness. However, challenges are identified, including internal issues related to information technology readiness and external constraints such as aligning service schedules with community preferences. This research contributes valuable insights to public service enhancement, emphasizing the need for adaptive strategies in addressing internal and external obstacles. Highlight : Comprehensive Analysis: The study provides an in-depth examination of Population Administration Services, offering a holistic perspective on its implementation and impact on rural governance. Service Quality Evaluation: Through interviews, the research evaluates service quality based on nine crucial elements, providing insights into the effectiveness of Population Administration Services. Challenges and Implications: Identified internal and external constraints, such as information technology readiness and service scheduling, highlight the need for adaptive strategies, contributing to the ongoing discourse on public service enhancement Keywords: Population Administration Services, Village Government Performance, Rural Governance, Public Service Enhancement, Qualitative Descriptive Research.